Modeling and Control Aspects of Wind Power Systems - Muyeen, S. M.; Al-Durra, Ahmed; Hasanien, Hany M. (IntechOpen, 2013)
This book covers the recent development and progress of the wind energy conversion system. The chapters are contributed by prominent researchers in the field of wind energy and cover grid integration issues, modern control theories applied in wind energy conversion system, and dynamic and transient stability studies. Modeling and control strategies of different variable speed wind generators such as switched reluctance generator, permanent magnet synchronous generator, doubly-fed induction generator, including the suitable power electronic converter topologies for grid integration, are discussed. Real time control study of wind farm using Real Time Digital Simulator (RTDS) is also included in the book, along with Fault ride through, street light application, integrated power flow solutions, direct power control, wireless coded deadbeat power control, and other interesting topics.